Scrub Typhus in Hospitalized Children. Issue 2 (March 2015) - Devarajan, Vidyalakshmi; Nambi, P. Senthur; Gopalakrishnan, Ram; Murali, Alagesan
<x xml:space="preserve">Abstract</x> Background Scrub typhus, caused by Orientia tsutsugamushi (formerly classified as Rickettsia tsutsugamushi), is an acute infectious disease of variable severity that is transmitted to humans by an arthropod vector of the Trombiculidae family. It affects people of all ages including children. It may be missed in this population unless clinically suspected. Materials and Methods We reviewed medical records of children admitted with scrub typhus between January 2010 and June 2012 in a tertiary care pediatric referral hospital. Scrub typhus was confirmed by a positive Detect TM immunoglobulin M enzyme-linked immunosorbent assay (In Bios International, Inc). This enzyme-linked immunosorbent assay detects immunoglobulin M antibodies in the human serum to O. tsutsugamushi–derived recombinant antigen (1–10). Results Twelve cases were analyzed during this period. The mean age was 8.25 years, with 7 male and 5 female patients. Fever was present in all 12 patients, followed by abdominal pain/vomiting in 7 (58.3%), headache in 4 (33.3%), rash in 3 (25%), and cough in 3 (25%). The mean duration of symptoms before presentation was 9 days. An eschar was present in 4 (33.3%). Thrombocytopenia was noted in 11 (90%). Splenomegaly on examination was present in 10 (83.3%). Five were treated with azithromycin; 4, with doxycycline; and 3, with both. Three of the 12 required intensive care unit stay. Conclusions Scrub typhus in children should be considered in all hospitalized children, especially if there is a recent rural or outdoor exposure, an eschar, splenomegaly, or thrombocytopenia. Unlike adults, renal dysfunction and central nervous system involvement seem to be uncommon. All children recovered after treatment with azithromycin, doxycycline, or the combination.